Increasing the Duration of On-Task Behavior in Children with Borderline Intellectual Functioning through Shaping Techniques - Putri, Dyah Ayu Dewianti; Kuntoro, Ike Anggraika (Universitas Medan Area, 2024)
This study aims to investigate and apply behavior modification principles, specifically using shaping techniques, to increase the duration of on-task behavior in children with Borderline Intellectual Functioning (BIF). The techniques used include antecedent control, reinforcement through token economy, and providing prompts to the participant. This study uses a single-subject design conducted over a total of 22 intervention sessions. The participant in this study is an 8-year and 7-month-old boy with BIF. The results of the study indicate an increase in the average duration of on-task behavior from 19 minutes in the initial measurement (pre-test) to 64 minutes in the final measurement (post-test) and 54 minutes in the follow-up measurement. It can be concluded that behavior modification principles, specifically using shaping techniques, can help to improve on-task behavior duration in children with Borderline Intellectual Functioning.